Plasma Chemistry and Gas Conversion - Britun, Nikolay; Silva, Tiago (IntechOpen, 2018)
Low-temperature non-equilibrium gaseous discharges represent nearly ideal media for boosting plasma-based chemical reactions. In these discharges the energy of plasma electrons, after being received from the electromagnetic field, is transferred to the other degrees of freedom differently, ideally with only a small part going to the translational motion of heavy gas particles. This unique property enables the important application of non-equilibrium plasmas for greenhouse gas conversion. While the degree of discharge non-equilibrium often defines the energetic efficiency of conversion, other factors are also of a great importance, such as type of discharge, presence of plasma catalysis, etc. This book is focused on the recent achievements in optimization and understanding of non-equilibrium plasma for gas conversion via plasma modeling and experimental work.